On the stability of the third order partial differential equation with time delay - A. Ashyralyev; S. Ibrahim; E. Hincal (Қарағанды университетінің хабаршысы. Математика сериясы)
In this paper, the initial value problem for a third-order partial differential equation with time delay within a Hilbert space was analyzed. We establish a key theorem regarding the stability of this problem. Additionally, we demonstrate how this stability theorem can be applied to the third-order partial differential equation with time delay.